The Natural History, Distribution, and Conservation of Lonely Rainfrogs, Pristimantis eremitus - Hutter, Carl (2016)
Natural history and behavioral information for species of the genus Pristimantis is scarce. We conducted an extensive study of Pristimantis eremitus, a vulnerable species for which there is scant biological information. We monitored 17 individuals for movements and intraspecific interactions for 13 mo. We describe the species' variation in dorsal color and pattern, which we used to uniquely identify individuals during the study. We also present results on the habitat utilization and home range of this species, providing evidence that this species shows a preference toward the bromeliad microhabitat when compared with other microhabitat types. We also describe the advertisement call and associated behaviors of the species. We update the known distribution of the species. Our data provide a baseline for future researchers to survey and identify individuals of P. eremitus, and which could be applied comparatively to other species where little of their natural history is known. We also show how an in-depth in situ study can provide useful information for species conservation. © 2016 by The Herpetologists' League, Inc.